Learning cycle 9E integrated with instructional videos for enhancing numeracy literacy among prospective mathematics teachers: A quasi-experimental study - Siska Andriani; Rizki Wahyu Yunian Putra; Indah Resti Ayuni Suri; Abi Fadila (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Numeracy literacy is a fundamental competency that enables prospective mathematics teachers to interpret, analyze, and apply mathematical knowledge in authentic contexts. However, conventional mathematics instruction often emphasizes procedural proficiency rather than contextual reasoning, resulting in limited numeracy literacy development. Integrating constructivist learning with technology-enhanced instruction offers a promising approach to addressing this challenge. Aim: This study aimed to investigate the effectiveness of the Learning Cycle 9E model integrated with instructional videos in enhancing the numeracy literacy of prospective mathematics teachers. Method: A quasi-experimental study employing a pretest–posttest control group design was conducted with 50 undergraduate students enrolled in the Mathematics Education Study Program at Universitas Islam Negeri Raden Intan Lampung, Indonesia. Participants were assigned to an experimental group (n = 25) and a control group (n = 25). Data were analyzed using descriptive statistics, Shapiro–Wilk and Levene’s tests, normalized gain (N-Gain), an independent samples t-test, and Cohen’s d effect size. Results: The experimental group outperformed the control group, achieving a higher posttest mean score (84.16 vs. 71.04) and N-Gain (0.62 vs. 0.31). A significant difference was identified between the groups (t = 6.485, p < .001), accompanied by a large effect size (d = 1.84). Conclusion: Integrating the Learning Cycle 9E model with instructional videos effectively enhances numeracy literacy by fostering active knowledge construction, contextual mathematical reasoning, and meaningful technology-enhanced learning experiences in higher mathematics education.